PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN PENALARAN MATEMATIS - Pasalbessy, Chyntia; Mataheru, Wilmintjie; Ayal, Carolina Selfisina (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2020)
The mathematical problem solving ability is important for students to solve problems in mathematics learning. The purpose of this study was analyzed the difference in improvement of mathematical problem solving ability between students who use STAD type of cooperative learning model and direct teaching. This type research is experimental research with a quantitative appoarch. The subjects in this study were eighth-grade students of the SMP Kalam Kudus Ambon in the first semester of the 2019/2020 academic calendar, which consisted of two classes. Methods of data collection through an Initial Ability Mathematics test and a mathematical problem solving ability test. The result showed that there was a difference increase in ability of problem solving between students who obtain learning by using the STAD type cooperative learning models and direct teaching